A secure dynamic quantum anonymous secret sharing protocol utilizing GHZ states - Wang, Qing-le; Wang, Ying-ying; Li, Yuan-cheng; Li, Guo-dong; Han, Yun-guang; Cheng, Long (Physica scripta, 2024)
Quantum secret sharing enables participants to share secrets grounded in the principles of quantum mechanics, ensuring the secrets recovery solely through collaborative efforts within an authorized subset of participants. Quantum anonymous secret sharing fulfills the fundamental requirements of quantum secret sharing while also ensuring the anonymity of the secret receivers. In order to address the turnover of personnel in practical scenarios, this paper propose a secure dynamic quantum anonymous secret sharing protocol utilizing Greenberger-Horne-Zeilinger states. In our scheme, on the premise of not reveal the identities of participants, the dynamic update of the participants can be realized, and the shared secret will not be altered. Furthermore, an identity authentication mechanism using single particles is introduced in this protocol, ensuring that only authenticated participants can engage in the sharing process. The proposed protocol is secure and can resist both internal and external attacks. Experimental validation conducted on the IBM quantum computing platform demonstrates the feasibility of our scheme.